(untitled) (Research, Society and Development, 2020)
Objective: to elaborate and validate a proposal for a care plan based on the North American Nursing Diagnosis Association-International, Nursing Interventions Classification, Nursing Outcomes Classification for diagnoses in the domain of coping and stress tolerance, identified in people living with the Acquired Immunodeficiency Syndrome. Method: methodological study, carried out with 25 specialists and 113 people living with Acquired Immunodeficiency Syndrome. These steps followed: elaboration of Nursing Diagnoses, Interventions and results; elaboration of a care plan and content validation by focus group. Results: a care plan containing 4 nursing diagnoses (Anxiety; Change stress syndrome; Fear; risk of feeling helpless) was validated, 4 results, 20 indicators, 4 interventions and 31 activities. Conclusion: the diagnoses, results and interventions found enabled the elaboration and validation of a care plan for people living with Acquired Immunodeficiency Syndrome